Dam cascade alters taxonomic composition of benthic macroinvertebrate community in upper Yangtze River. (16th March 2021) - Zhang, Hui; Zhu, Chenxi; Mo, Kangle; Chen, Qiuwen; Tang, Lei; Zhang, Jianyun; Li, Ting; Wang, Jun
Abstract: Cascade dams segment river connectivity, modify the hydrological process, and change the hydraulic properties, thus influencing the river ecosystem significantly. Ecological effects of dams have been extensively studied, but investigations on zoobenthos in a large area covering tributaries and mainstream with cascade dams are lacking. Here, we studied the features of benthic macroinvertebrate assemblages in the lower Jinshajiang River, which is the upper reach of the Yangtze River. Over 15, 000 macroinvertebrate individuals were collected in the mainstream and eight tributaries. Altogether, 105 taxa belonging to 19 orders and 55 families were identified. The structure of benthic macroinvertebrate assemblages was considerably different between the natural‐flow reach and the reservoir reach in the mainstream. The diversity and abundance of Ephemeroptera, Trichoptera, and Megaloptera decreased to almost zero as a result of dam impoundment. By contrast, the abundance of Diptera, Chironomidae, and Tubificida increased significantly in the mainstream reservoir reach. The diversity of macroinvertebrate species in the mainstream reservoir reach was only half of that in the natural‐flow mainstream. The difference between macroinvertebrate assemblages in natural‐flow mainstream and tributaries was insignificant. Therefore, dam construction was considered the main cause of macroinvertebrate assemblage changes. Our results highlighted the necessity of maintaining sufficient natural river sections between cascade reservoirs to conserve the biodiversity of benthic macroinvertebrate.